The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/ebr-03-2018-0060
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic capabilities

Abstract: Purpose The growth, diversity and applications of research into dynamic capabilities (DCs) have resulted in the whole literature on DCs becoming a complex and disconnected body of knowledge. This has led to criticisms of the subject of DCs as being vague, tautological and without practical value. Hence, the purpose of this paper is to synthesize the diverse scholarly literature about DCs and develop a more integrated understanding to minimize the reported apparent vagueness. Design/methodology/approach In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 178 publications
(349 reference statements)
2
27
0
1
Order By: Relevance
“…The results suggest that GIC proxies such as product and process innovation have significant effects on manufacturing firms' GCA in China. The results support Eisenhardt and Martin (2000) findings which revealed that innovation culture is fundamental to enhancing the firm's ability to maintain competitive advantage. It further asserts the findings of (Chen, 2008) who revealed that Green product and process innovations are related to the innovation of products involving environmentally friendly material, packaging, recovery of products and recycling, eco-labeling and innovation in a firm's ability to improve existing processes, develop new processes that create savings and prevent pollution, enhance energy savings, prevent pollution, increase waste recycling.…”
Section: Direct Model 1 Gic On Gcasupporting
confidence: 84%
See 1 more Smart Citation
“…The results suggest that GIC proxies such as product and process innovation have significant effects on manufacturing firms' GCA in China. The results support Eisenhardt and Martin (2000) findings which revealed that innovation culture is fundamental to enhancing the firm's ability to maintain competitive advantage. It further asserts the findings of (Chen, 2008) who revealed that Green product and process innovations are related to the innovation of products involving environmentally friendly material, packaging, recovery of products and recycling, eco-labeling and innovation in a firm's ability to improve existing processes, develop new processes that create savings and prevent pollution, enhance energy savings, prevent pollution, increase waste recycling.…”
Section: Direct Model 1 Gic On Gcasupporting
confidence: 84%
“…It involves adopting processes that save energy, reduce pollution and allow for waste recycling (Chen, 2008). The concept of innovation has been critical in creating a corporate competitive advantage (Eisenhardt and Martin, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic refers to the capacity of a firm to renew its existing competencies to handle a changing environment. Capabilities refer to strategic management's vital role in integrating, adapting or reconfiguring the firm's internal and external competencies and resources to match the changing environment (Sunder et al, 2019). Teece's (2007) approach elaborated on Teece et al's (1997) typology, which is seminal to the study of DCs (Schilke et al, 2018).…”
Section: Dynamic Capabilitiesmentioning
confidence: 99%
“…Seizing is evaluating existing capabilities and resources and making investments for procuring assets (Fainshmidt et al, 2019). Reconfiguring is altering the firm's existing operational capabilities to handle a rapidly changing environment (Sunder et al, 2019). A firm achieves a sustainable competitive advantage when it becomes an expert in these three capabilities (Teece, 2007;Kay et al, 2018).…”
Section: Dynamic Capabilitiesmentioning
confidence: 99%
“…The resource-based view emphasizes that resources and capabilities are important factors for firms to develop competitive advantages that eventually drive innovation (Barney, 1991; Kristandl and Bontis, 2007; Sunder et al , 2019). Then, what factors drive firms to innovate processes?…”
Section: Introductionmentioning
confidence: 99%